The relationship between corporate governance and dividend payout ratio: Evidence from Malaysia - Musa, Shehu (2014)
The main objective of this study is to find the relationships between corporate governance mechanisms and dividend payout ratio among the Malaysian public listed companies. A sample of 164 Malaysian companies for the year 2013 was selected from the Bursa Malaysia website. This study examines the relationships between board compositions, board size, CEO Duality, proportion of family members on the board, direct ownership, institutional ownership, concentrated ownership as the corporate governance variables and dividend payout ratio among the Malaysian public listed companies. The control variables include leverage, firm size, and profitability while the dividend payout ratio as the dependent variable. The findings of this study show that only institutional ownership and concentrated ownership are found to be positive and significant in influencing the dividend payout ratio. But, the independent director is also found to be significant in influencing the dividend payout ratio in negative direction. The finding of this study will enhance the literature in the field for future studies and will also be worthwhile for the companies, investors as well as the policy makers and regulators in Malaysia by providing information on the effectiveness of some corporate governance mechanisms that influence the firm dividend payout ratio after the implementation of revised Code on Corporate Governance 2012 to make important recommendations for the improvement in the corporate governance practices in Malaysia and to safeguard the interest of minority shareholders.